Discerning Natural and Anthropogenic Factors Driving the Variation of Estuarine CH4 and N2O - Zhengping Chen; Liuqian Yu; Qichun Yang; Qixing Ji (Ocean-Land-Atmosphere Research)
Estuaries are commonly recognized as a major source of greenhouse gases due to the massive anthropogenic input of organic matter and nutrients, which is associated with highly active microbial assemblages. However, the combined effects of natural and anthropogenic factors and their relative contributions to estuarine greenhouse gas emissions are not well understood, particularly at the confluence of fresh water and seawater. In this study, biweekly sampling was conducted from November 2021 to January 2024 at the main outlet of the Pearl River in south China, which is characterized by a subtropical climate, a eutrophic environment, and heavy anthropogenic activity. Measurements were obtained of the dissolved methane (CH4), nitrous oxide (N2O), and associated seasonally varying physical and chemical parameters at a high temporal resolution. Analysis of the measurement data revealed that the dissolved CH4 and N2O concentrations were decreased by increases in the river discharge, which enhanced the dilution effect, and reductions in anthropogenic activities, such as the enforcement of measures to prevent COVID-19. The different dynamic processes of the nitrogen and carbon cycles may have contributed to the differences in the variations of the CH4 and N2O concentrations (e.g., N2O varied within a narrower range than CH4). By presenting and analyzing the 2-year time series of estuarine CH4 and N2O with a high temporal resolution under complex natural and anthropogenic forcing, this study underscores the importance of human influence on greenhouse gas inventories and emissions.